VD_FINDINFO Jug / 2012 / 256 vom 3. Mai 2012 - VD Tribunal cantonal (2012)
ACTE D'ORDRE SEXUEL AVEC UN ENFANT, APPRÉCIATION DES PREUVES, VIOL, FIXATION DE LA PEINE | 187 ch. 1 CP, 190 al. 1 CP, 47 CP, 10 CPP (CH)